Two coordination polymers of benzene-1, 2, 4, 5-tetracarboxylic acid (H4BTC): in situ ligand syntheses, structures, and luminescent properties1. Issue 18 (14th May 2015) - Zhong, Di-Chang; Guo, Hua-Bin; Deng, Ji-Hua; Chen, Qing; Luo, Xu-Zhong
<x xml:space="preserve">Abstract</x> For the first time, two new benzene-1, 2, 4, 5-tetracarboxylic acid based coordination polymers have been constructed through in situ hydrolysis reaction. Their gas sorption and luminescent properties have been investigated.